APLIKASI PENGINDERAAN JAUH UNTUK ANALISIS DAN IDENTIFIKASI KALDERA DI KABUPATEN KULONPROGO DAERAH ISTIMEWA YOGYAKARTA - , PIUS ERDWIN G P P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Software usage in the study of geological sciences are increasingly needed to make geological tasks both indoor and outdoor became much easier. The main superiority of this method is its practical. This research is planned to measure how good are softwares capability in processing geological data. The research area is located in Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta. According to the past research, most of research area are Old Andesite of Bemmelen Formation which is dominated by volcanic processes and estimated as an aged eroded caldera. Some softwares are being used ini this research to analyze several kinds of remote sensing data. ArcGIS is used to analyze morphology and slopes with some functions called hillshade, slope, and aspect. PCI Geomatica Focus has an ability to automatically extract lineament data from a raster image. Which then used to analyzed the general direction of the force that controls that area. ER Mapper is used to process landsat image which will displays appearance that suit the type of analysis. Those output are then combined and analyzed with automatic or manual method to provide the information we need. The result shows that the morphology and lineament in the research area are basically rounded and some of them characterize a parts of caldera such as outer wall, inner wall, topographic rim andresurgent dome